Implementation of Distributed File System on Object Group Platform "Jgroup" (Journal of Hama University, 2019)
Distributed systems building techniques aims to interact the application components which are placed on different machines and connected through a network. The increasing reliance on these systems in day-to-day activities requires that their techniques to provide available and reliable services. Neither RMI nor CORBA can achieve this requirement; because they cannot support one-to-many interaction.Jgroup provides dependable services through its integration of object group paradigm with the distributed object model of Java RMI, so it offers a Group Communication System depends on RMI in all its interactions; whether internal for coordination between object group replicas, or external for communicating clients with object group.This paper implements a distributed file system benefits of all provided facilities of Jgroup in performing the main operations (list all files, download a file, upload a file, and modify          a file).This research evaluates performance of the system through measurement of delay required to upload files of different sizes from clients; with increasing the number of servers.In addition to evaluation of performance through measurement of delay required to download a file with increasing the number of clients' requests. Results show that the delay for uploading a file increases with increasing number of servers in object group, and the delay for downloading a file doesn't affected by increasing the number of clients' requests.